Acceptance of psoriasis in the context of body image, body experience, and social support - Olga Sakson-Obada; Mariola Pawlaczyk; Katarzyna Gerke; Zygmunt Adamski (Health Psychology Report, 2017)
Background Acceptance of disease is an important determinant of quality of life in psoriasis patients. Social support and positive body image are considered important contributors to coping with the disease, but no studies have yet examined the role of body image and body experience in relation to psychological adjustment to psoriasis. We aimed to identify the role of biopsychosocial aspects – medical characteristics, body image, body experience, and social support – in acceptance of psoriasis.